The Greek Version of the Blended Teaching Readiness Instrument (BTRI) - Angelos Giannoulas; Antonios Kalamatianos; Kalliopie Kounenou (Online Learning)
During the Covid-19 pandemic education systems policy makers realized the importance of being able to communicate using technology and, at the same time, to maintain their pursuits. As a consequence, a different approach to education followed, blended learning.